The phenomenon of preventing Asian and African members from assuming the FIFA presidency: an analytical study of rights and the election process - Abbas Al-Jabouri, (المجلة الدولية للبحوث والدراسات القانونية, 2026)
This paper examines the issue of the continued denial of the presidency of the International Federation of Football Association (FIFA) since its establishment in 1904, despite the fundamental transformations that the global football system has witnessed in terms of the numerical expansion of the member associations, the geographical spread, and the mass and economic weight of the two continents. The research is based on the hypothesis that elections within FIFA, despite their formal legal legitimacy, have historically not served as a neutral mechanism for the rotation of power, but have turned into an institutional pretext for the reproduction of leadership dominance European-rooted.The research relies on the historical-analytical and descriptive-analytical approaches, by tracing the evolution of the leadership structure within FIFA, analyzing the electoral system and its undeclared mechanisms, and revealing structural flaws in leadership representation. The research also discusses the human rights dimension of exclusion, highlighting the contradiction between FIFA's value discourse on inclusivity and non-discrimination, and its actual practices at the leadership level.The research highlights the importance of the Asian-African People's Movement as a moral and media pressure tool capable of transferring the issue from its closed institutional framework to the space of global public opinion, thus contributing to the accountability of the legitimacy of the current leadership and pushing for reforms in governance and the electoral system. The research concludes that achieving representative justice in the FIFA leadership is not only a symbolic requirement, but also a prerequisite for enhancing the organization's credibility and consolidating the principles of good governance in global football.